Low cost housing : an evaluation of its adequacy in relation to the Coloured group in Cape Town - Lipman, Leonard Ivan (School of Architecture, Planning and Geomatics, 2020)
"No single element in urban planning outweighs in importance that of housing for the well being of the individual, the family and the community. Yet few questions in urban planning are as little understood, as subject to varying standards and as open to emotionally charged argument as that of what constitutes 'adequate' and 'inadequate' urban residential environments". Whilst housing presents a universal problem, it assumes special importance and significance for South Africa. In this country, Non-Whites constitute 81 per cent of the total population and the large majority of them, who fall within the lowest income groups, are unable to provide themselves with adequate housing. In Cape Town, the Non-White population consists largely of the Coloured group. Although Westernised and becoming increasingly urbanised, this group occupies a differentiated position, in the economic, social and political structure of Cape Town's society